Differences in performed actions of winners and defeated female cadet wrestlers in a standing position - Kajmovic, H.; Rado, I.; Kapur, A.; Mekic, A.; Kapo, S. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
PURPOSE: Wrestling is very intense polystructural acyclic activity in which female wrestlers have the possibility to win or be defeated based on their current performances. For this reasons, athletes and coaches must understand the demands of wrestling in competition as well as the significance of the informations collected by notation analysis at the competition, which are later analyzed in purpose of improving wrestling performances on a higher, better level. The purpose of this research is determining differences in performed wrestling technical actions of winners (W) and defeated (D) female cadet wrestlers in a standing position at European cadet championship for male and female cadets. METHODS: The sample of subjects consists n=267 throwing technique from which the winners achieved n=203, and defeated contestants n=67 throwing techniques. The sample of variables are all from standing throwing techniques which were successfully applied during the fight, and the judges, based on that efficiency, gave adequate points. The data were collected based on notation analysis of videos at European championship for cadets, held in Sarajevo (Bosnia and Herzegovina) in 2010. in all weight categories for cadets. In order to identify differences in accomplished perormances between winners and defeated contestants, the Wilcoxon rank test was used, at the level of statistical significance of p 0.05. RESULTS: The results of Wilcoxon rank test showed that the winners dominate in comparison to defeated wrestlers in the following techniques in the standing position: Take down (p<.001) W=70,9% - D=29,1%, Push out techniques (p=.013) W=84,6% - D=15,4%, Throw with both legs locked (p=.002) W=92,3% - L=7,7%, A Fireman's carry (p=.011) W=90,0% - D=10,0%, Pulling down (p=.014) W=100,0% - D=0,0%, Side throws (p<.001) W=99,4% - D=5,6%, while in counterattack techniques in standing position (p=.157) and Sholder throw with no significant difference (p=.157). CONCLUSION: The value of the data collected indicate that, in cadet phase on this level of competition, individual wrestling techniques significantly dominate over other wrestling techniques. By far the most effective techniques, used by winners and defeated contestants, is Take down technique, and after it, Side throws. It is clear that the contestants inexperience, technical exellence and fitness levels contributed to the differences between winners and defeated contestants. Based on the results, this type of collecting data about performance levels is repeatable, and based on this, coaches can design new programs of training that will improve the performance of contestants, both in attack and in defense.